Strategi Bertahan Pedagang Sayuran di Pasar Tradisional Pelita Kaliwates Jember di Masa Covid-19 - Jovanka, Delina Tavaria; Kurniawan, Deddy (KUBIS, 2023)
The Pelita market is always busy every day with buyers, but due to the current condition of the Covid-19 pandemic, it has an impact on economic activity at the Pelita market. This resulted in a decrease in the total income of traders. To survive during the Covid-19 pandemic, traders carried out a survival strategy to continue to generate income. This study uses qualitative research methods, the type of research is field research with a descriptive approach. The data collection techniques are through observation, interviews, and documentation. Data analysis techniques used pre-field analysis and data analysis in the field with the stages of data reduction, data presentation, and concluding. Test the validity of the data using source triangulation. The results showed: 1) Active strategy, by increasing the quality of goods and services, having family members who help work, and increasing working hours, 2) Passive strategy, namely by reducing merchandise inventory, reducing the number of employees, 3) Network strategy, by establishing good relationships with buyers, depositing merchandise at nearby stalls, as well as doing a side online business.